ANALISIS KEBERADAAN RHODAMIN B PADA SAUS TOMAT YANG BEREDAR DI PASAR KOTA PALEMBANG - Amelia, Rizky; Zairinayati, Zairinayati (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
Coloring substances in food are generally classified into two categories, namely natural dyes and synthetic dyes. Rhodamine B is a synthetic dye which is widely used in the textile industry. The use of Rhodamine B in food can cause irritation to digestion, inhalation, and eyes. This research was conducted to detect rhodamine B content in tomato sauce by adding detergent. The design of this study was a qualitative descriptive study conducted on tomato sauce on the market. The test results for the presence of rhodamine B in tomato sauce with the addition of detergent solution showed that from 6 samples examined, there were 4 samples that had a color change from bright red to pale red. The color change indicates that there is Rhodamine B in tomato sauce. Positive tomato sauce contains the harmful dye rhodamine B using a detergent solution as a medium to determine the content of synthetic dyes qualitatively.